2007
DOI: 10.1158/0008-5472.can-06-2306
|View full text |Cite
|
Sign up to set email alerts
|

Antiadhesive Effects of GRN163L—An Oligonucleotide N3′→P5′ Thio-Phosphoramidate Targeting Telomerase

Abstract: We determined previously that a novel human telomerase RNA (hTR) antagonist, GRN163L, inhibited the tumorigenic potential of A549-luciferase (A549-luc) lung cancer cells in vitro and in vivo. Further studies revealed that A549-luc cells were also morphologically altered by GRN163L. A549-luc cells treated before cell attachment with a single dose of GRN163L only weakly attached to the substrate and remained rounded, whereas control mismatch-treated cells exhibited typical epitheloid appearance and adhesion prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 31 publications
3
48
0
2
Order By: Relevance
“…35 When we attempted to achieve a more complete telomerase blockade by increasing the imetelstat concentration (8 and 16 mM), cells showed immediate toxicity, likely the result of extra-telomeric effects of imetelstat such as decreased cell adhesion and disruption of the cytoskeleton. 36,37 Such effects may be desirable for treating cancer cells, but for the purpose of the current investigation, we chose to limit the concentration of imetelstat to focus on effects related to telomere shortening.…”
Section: Discussionmentioning
confidence: 99%
“…35 When we attempted to achieve a more complete telomerase blockade by increasing the imetelstat concentration (8 and 16 mM), cells showed immediate toxicity, likely the result of extra-telomeric effects of imetelstat such as decreased cell adhesion and disruption of the cytoskeleton. 36,37 Such effects may be desirable for treating cancer cells, but for the purpose of the current investigation, we chose to limit the concentration of imetelstat to focus on effects related to telomere shortening.…”
Section: Discussionmentioning
confidence: 99%
“…Our data support a role for telomerase in ependymomas in allowing proliferation as hTERT expression correlated with both increased mitotic index and MIB-1 proliferative index in our ependymoma cohort (Table 3). This is important as a variety of studies (De Semir et al, 2007;Jackson et al, 2007) have suggested other roles for telomerase in proliferating cells. Telomere maintenance in paediatric ependymomas U Tabori et al Furthermore, our data support a role for telomerase in protecting cells from DNA damage by demonstrating an inverse correlation between hTERT and gH2AX expressions (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…GRN163L is a modified oligonucleotide complementary to hTERC and a potent and specific telomerase antagonist 66 . GRN163L effectively inhibits telomerase activity of various human cancer cell lines [67][68][69][70] , resulting in progressive telomere shortening and induction of cellular senescence to suppress tumor cell growth in vitro. Furthermore, administration of GRN163L is effective in preventing lung metastases in breast cancer xenograft animal models 68 .…”
Section: Future Anti-cancer Therapy: Therapeutic Strategies That Targmentioning
confidence: 99%